Role of comprehensive diabetes care in known diabetes patients from western Mumbai region: an observational study - Sane, Rohit; Mandole, Rahul; Amin, Gurudatta Anand; Ghadigaokar, Pravin; Paranjape, Sneha; Gond, Bipin; Asnodkar, Prajakta; Badre, Aarti; Shinde, Supriya; Ahmed, Amirullah (International Journal of Research in Medical Sciences, 2020)
Background: The occurrence of Diabetes Mellitus (DM) has been creating a havoc since past few decades on a global platform. As per available literature, prevalence of DM in Mumbai is around 10%. Comprehensive Diabetes Care (CDC) is a form of Ayurvedic therapy which combines panchkarma and diet management. The present study was planned to evaluate the effectiveness of CDC in patients of DM by analysing changes in body mass index (BMI), body weight, OGTT, HbA1c, etc. Methods: The present study was of retrospective design, conducted at Madhavbaug clinics in western Mumbai. The duration of study was of one year, conducted from October 2018 to September 2019. It included patients diagnosed with type 2 DM i.e. HbA1c>6.5%, who were given CDC therapy. Results: In the present study, out of 183 type 2 diabetic patients, 99 were males (52%), while 84 were females (48%), thus male: female ratio was 1.17:1. On analysing the results of HbA1c in patients who had completed 12 weeks of CDC therapy, it was found that controlled DM status was seen in 109 patients (59%), while uncontrolled DM status was noted in 33 patients (19%) as compared to 102 patients (58%) at baseline. Conclusions: From the findings of the present study, it is clear that CDC is effective in the form of increasing number of euglycemic patients at the end of study period, as well as reduction in all glycaemic and anthropometric parameters, and reducing dependency on conventional medicines.